A war of logistics parachutes and porters in Indochina, 1945-1954 - Shrader, Charles R. (Foreign military studies, 2015)
In A War of Logistics, Charles R. Shrader meticulously examines both French Union and Viet Minh logistical units during the period of active conventional warfare, as well as external support provided to the French by the United States and to the Vietnamese by China. Although the Vietnamese had few advantages over their opponents, their military leaders brilliantly employed a highly committed network of soldiers and civilians, outfitted to accommodate the challenging terrain on which they fought.